Stock Market Efficiency And Technical Trading Systems: A Study Of The Malaysian Stock Market - Tam , Kut Hing (2005)
This study attempts to shed light upon this controversy of the value of technical analysis by providing further empirical evidence as to whether technical trading can be used profitably. The efficient market hypotheis provides a theoretical basis to test it technical trading systems might work. This thesis examines 13 technical trading systems commonly used by Malaysian analysts, fund managers and investors. The mean returns from a sample of 38 KLCI linked stocks traded in and out on a technical basis are compared with the returns from a buy-and hold strategy for a seven year period from 1996 to 2002. Three sets of transaction costs are used to test the profitability of these 13 trading systems; the first set with zero transaction cost; the second set for retail trades at 0.84 percent and the third set for online trades at 0.44 percent.